(3cJGH GdYQhV GdHGQY HGdENJUGQ GdLGeYs - (3Ydj Hf LYaQ Hf Ydj GdSYOj, CHh GdbGSe, GdSYOj GdUbdj GdeUQj, GdeYQha H GHf GdbWGY,J (B515 (3g` s ((3GHh HcQ Hf CMeO Hf OGhO Hf SdjeGf GdYLei GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg MeO eYJQa HPfHg ebQ HGdhMOGfjI dQHg EYde Cf GdYQhV Yde hVY deYQaI ChRGf TYQ GdYQH s
(3BNQgG (B:s
(3HGH de jPcQg GdNdjd hgh aGYdf jJcQQ KeGf eQGJ hbO CJJ ajg CTYGQ cKjQI YfO aUMGA GdYQH hZjQge hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3GdYQhV hGdbhGais